DETERMINANTS OF ONLINE PURCHASE DECISIONS AT SHOPEE MARKETPLACE - B, Mesra; Hernawaty, Hernawaty; Asih, Surya (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This study aims to analyze the marketing mix on online purchasing decisions on the Shopee Marketplace at the student Universitas Pembangunan Panca Budi. The method used is collecting data through questionnaires with the criteria of consumers who have transacted on the Shopee online shopping site totaling 96 respondents. This research is a quantitative research using structural equation modeling (SEM). The results of this study conclude that: product, price, promotion, and distribution have a positive and significant effect on online purchasing decisions.